Psychology and World Heritage? Reflections on Time, Memory, and Imagination for a Heritage Context. Issue 2 (May 2020) - Benson, Ciarán
Abstract: Concepts of memory—specifically notions of collective memory—are associated in heritage studies with the central idea of authenticity. In this article I review what is relevant in the psychology of memory to these discourses, and reflect on this association of collective memory and authenticity in heritage studies, notably in the 1994 Nara Document on Authenticity. Concepts of time are central to this review. The idea of world heritage is, it is suggested, a future-oriented ideal for a common humanity. The metaphorical underpinnings of our vernacular uses of time-concepts, such as past and future, are examined. Psychological considerations of memory as retrieval or reconstruction are then outlined. The distinction between kinds of memory, notably episodic and semantic memory, is then presented. These, it is argued, are building blocks for collective memory, which, in turn, is the seedbed for the underemphasized but potent idea of collective imagination. If the primary function of memory is actually oriented to the future, then imagination is what puts kinds of memory to work in both predicting and creating the future. Our ability to imagine—to mentally project forward—is heavily dependent on what we know—that is, on semantic memory. The article concludes with some reflections on the policy implications of this analysis for the visitor to world heritage sites.